THE PREVALENCE AND DETERMINANT FACTORS OF LOW VITAMIN D LEVELS IN PATIENTS WITH PAINFUL DIABETIC NEUROPATHY - PINZON, RIZALDY TASLIM; PRADANA, ANDRYAWAN WAHYU; ANGELA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Type 2 diabetes mellitus is a major public health problem. Diabetic neuropathy is one of the major diabetes microvascular complications. The previous study suggests that Vitamin D deficiency plays an important role in the development and progression of diabetes and the data in Indonesia are very limited. This study aims to measure the prevalence of Vitamin D deficiency and its determinant factors in patients with painful diabetic neuropathy (PDN). Methods: This study is a cross-sectional study. The data were obtained from 53 subjects with diabetic peripheral neuropathy. A pre-designed questionnaire was used to collect data on the patient’s age, gender, duration of diabetes, comorbidities, any diabetic complications, and current treatment for diabetes mellitus. The Vitamin D levels were measured by a standardized method in the Prodia Research Laboratory. Results: Study findings showed that from 53 study subjects, most of them were female (79.2%). The mean age of subjects was 57.83±8.79 years. We found a high prevalence of low Vitamin D levels in the Indonesian population as many as 98.11% and only 1.9% has sufficiency Vitamin D levels. Gender (p=0.028), hypertension (p=0.027), and controlled complications (p=0.005) were significantly associated with Vitamin D levels. Conclusion: All patients with PDN in this study had a high prevalence of Vitamin D deficiency. This high prevalence of Vitamin D deficiency also has been reported worldwide. Physician should be aware and continue to treat patients with Vitamin D deficiency.